Supply Chain Risks and Resilience in Grains-Crop farming in North-Western Nigeria - Adewole , Adebisi; Sambo, Obed G. (International Journal of Scientific Research and Management (IJSRM), 2025)
Many small-scale grain-crop farmers in northern Nigeria encounter environmental, economic, political, and technological risks. This research investigates the farming supply chain value risks and assesses the resilience capacity of grains-crop farmers in North-Western Nigeria. Data gathering involved purposive sampling to conduct qualitative interviews. Findings suggest that poor infrastructure, activities of insurgent groups, unfavourable weather conditions, limited access to finance, high cost of inputs, and inadequate technologies are some of the major challenges facing small-scale grain farmers in northern Nigeria. Research advocates better support to farmers to help prevent risks or overcome the effects of risks. Training and adult literacy skills for rural farmholders are advocated in this work. Policies delivered to rural farmers will lower risks to farmers and support the ability for stronger resilience. This study adopted qualitative research which implies that the outcome will not represent all the smallholder farmers in North-Western Nigeria. Future researchers may adopt quantitative analysis to be more representative.